Ethanol steam reforming over cobalt talc in a plate microreactor - Domínguez, M. (2011)
Stainless steel plates were coated with cobalt talc (Co 3[Si 2O 5] 2(OH) 2) and used in a catalytic plate microreactor for producing hydrogen from ethanol steam reforming at low temperature. Cobalt talc was deposited successfully by one-step hydrothermal synthesis from Co(NO 3) 2·6H 2O and Na 2SiO 3 at 463K for 60h and characterized by scanning electron and confocal microscopy, X-ray diffraction, infrared spectroscopy, and mechanical stability tests. Catalytic plates did not require any activation treatment and showed fast start-up. At 648K and W/F EtOH=0.5gminmol -1 complete ethanol conversion was attained and the yield to the reforming products, H 2 and CO 2, was 97 and 90%, respectively, whereas CO was detected at a trace level (<0.1%).